Cefepime neurotoxicity: thresholds and risk factors. A retrospective cohort study. (March 2020) - Boschung-Pasquier, L.; Atkinson, A.; Kastner, L.K.; Banholzer, S.; Haschke, M.; Buetti, N.; Furrer, D.I.; Hauser, C.; Jent, P.; Que, Y.A.; Furrer, H.; Babouee Flury, B.
Abstract: Objectives: Toxic serum cefepime trough concentrations are not well defined in the current literature. We aimed to define a more precise plasma trough concentration threshold for this antibiotic's neurological toxicity and to identify individuals at risk for developing neurotoxic side effects. Methods: Retrospective study including all individuals who underwent cefepime therapeutic drug monitoring (TDM) between 2013 and 2017. Individuals with cefepime concentrations other than trough were excluded. The primary outcome was to assess the incidence of neurotoxicity and its relationship with cefepime plasma trough concentrations. Secondary outcomes were the relationship of renal function, cefepime daily dose, age, and cerebral and general co-morbidities with the occurrence of neurotoxicity. We also compared the mortality rate during hospitalization in individuals with and without neurotoxicity, and the possible impact of neuroprotective co-medications on outcomes. Results: Cefepime concentrations were determined in 584 individuals. Among 319 individuals with available trough concentrations included, the overall incidence of neurotoxicity was 23.2% (74 of 319 individuals). Higher cefepime plasma trough concentrations were significantly associated with risk of neurotoxicity (no neurotoxicity 6.3 mg/L (interquartile range (IQR) 4.1–8.6) versus with neurotoxicity 21.6 mg/L (IQR 17.0–28.6), p <0.001). Individuals with presumed cefepime neurotoxicity had a significantly lower renal function (estimated glomerular filtration rate 82.0 mL/min/1.73 m 2 (IQR 45.0–105.0) versus 35.0 mL/min/1.73 m 2 (IQR 23.3–53.3], p <0.001), and significantly higher in-hospital mortality (19 (7.8%) versus 26 (35.1%) individuals, p <0.001). No neurotoxic side effects were seen below a trough concentration of 7.7 mg/L. Levels ≥38.1 mg/L always led to neurological side effects. Conclusion: In individuals with risk factors for cefepime neurotoxicity, such as renal insufficiency, TDM should be systematically performed, aiming at trough concentrations <7.5 mg/L.